2021
DOI: 10.1021/acs.joc.1c02234
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazole-Mediated C–H Functionalization of Arene and Heteroarenes for Aryl–(Hetero)aryl Cross-Coupling Reactions

Abstract: Herein we introduce a transition-metal-free protocol that involves a commercially available, inexpensive pyrazole molecule to conduct C–C cross-coupling reactions at room temperature via a radical pathway. Using this method, an aryldiazonium salt has been coupled to a wide range of arenes and heteroarenes including benzene, mesitylene, thiophene, furan, benzoxazole to result the corresponding biaryl products. The full reaction mechanism is elucidated along with the crystallographic probation of an active initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…26,27 Some previous reports including our recent work showcased the potential of aromatic heterocycles in their deprotonated form. 28 We reasoned that the deprotonated form of 9,10dihydrophenazine (L1, Scheme 1) may be suitable for promoting electron transfer to a substrate molecule. 28 The deprotonation of L1 is fully feasible under basic conditions as the measured pKa is 5.5 in DMSO medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Some previous reports including our recent work showcased the potential of aromatic heterocycles in their deprotonated form. 28 We reasoned that the deprotonated form of 9,10dihydrophenazine (L1, Scheme 1) may be suitable for promoting electron transfer to a substrate molecule. 28 The deprotonation of L1 is fully feasible under basic conditions as the measured pKa is 5.5 in DMSO medium.…”
Section: Resultsmentioning
confidence: 99%
“…28 We reasoned that the deprotonated form of 9,10dihydrophenazine (L1, Scheme 1) may be suitable for promoting electron transfer to a substrate molecule. 28 The deprotonation of L1 is fully feasible under basic conditions as the measured pKa is 5.5 in DMSO medium. We further anticipated that L1 can be converted to its fully aromatic form, phenazine, upon undergoing the 2e − /2H + process, so there could be a thermodynamic driving force behind such electron transfer processes.…”
Section: Resultsmentioning
confidence: 99%
“…The discussed SET from the redox‐active o ‐phenylenediamido backbone is an analogous event. Furthermore, we have also observed that electron rich anion of 3,5 dimethyl pyrazole can facilitate SET process to aryldiazonium chloride to break the bond homolytically resulting the generation of aryl radical [26] . However, the reduction potential of aryldiazonium salts is much positive to a moderately strong Ar−Br bond.…”
Section: Resultsmentioning
confidence: 85%
“…In 2021, Adhikari's research group [58] reported the use of a new SED in synthesis of biaryl compounds from aryldiazonium salts 1 and (hetero)‐arene compounds 20 (Scheme 24b). The organic molecule used as additive was 3,5‐dimethylpyrazole 64 in conjunction with KO t Bu.…”
Section: Aryl Radicals From Aryldiazonium Salts Under Thermal Conditionsmentioning
confidence: 99%